The effect of Mn on flame spray pyrolysis-made ZnO nanoparticles for flammable gases detection - Tamaekong,N. (American Scientific Publishers, 2015)
Copyright © 2014 American Scientific Publishers. All rights reserved. The application of Mn-loaded ZnO nanoparticles to the design of flammable gas sensors is nowadays one of the most active research fields, due to their high activity, good adsorption characteristics and high selectivity with high response to toxic and combustible gases. It is sensitive to many gases at moderate temperature, such as C2H4, CH4 and C2H2 gases. FSP presents a new technique for 0.25-1.00 mol% Mn-loaded ZnO nanoparticles synthesis which involves only a single step. The crystallite sizes of ZnO spherical and hexagonal particles were found to be ranging from 5 to 15 nm while ZnO nanorods were seen to be 5-15 nm in width and 20-40 nm in length. In addition, very fine Mn nanoparticles were uniformly deposited on the surface of ZnO particles. The highest response for CH4 gas was ∼240 towards 0.50 mol% Mn-loaded ZnO at 1.0 vol.% concentration of CH4 in dry air at 300 °C. The response of 0.50 mol% Mn-loaded ZnO of C2H4 gas was as high as 72 for 1.0 vol.% while the response for C2H2 gas was ∼13 towards 0.50 mol% Mn-loaded ZnO at 1.0 vol.% concentration of C2H2 in dry air at 300 °C.